2022
DOI: 10.29408/ab.v3i1.5852
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan analisis SWOT untuk memahami kondisi internal dan eksternal

Abstract: The times have increased competition in all sectors of life. Along with the progress of the times, science also continues to grow. Knowledge is used to answer various human needs, increasingly fierce competition in organizations that require various strategies to survive and win the competition. SWOT analysis is one of the sciences used to produce this strategy (Strength=Strength, Weakness=Weakness, Opportunity=Opportunity, Threat=Threat). This analysis is to see the internal and external conditions of an orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Other trials have also revealed differences in susceptibility, indicating possible genetic resistance within host populations (Breton et al, 2006;Idris et al, 2004). The existence of resistant genotypes has also been indicated in trials of 20 DxP crosses in Indonesia (Purba et al, 1994) and in E. oleifera x E. guineensis hybrids in Malaysia (Chung et al, 1994). Thus, resistant materials view as an outstanding promise for future management of BSR in oil palm in SEA (Breton et al, 2006;Durand-Gasselin et al, 2005;Idris et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other trials have also revealed differences in susceptibility, indicating possible genetic resistance within host populations (Breton et al, 2006;Idris et al, 2004). The existence of resistant genotypes has also been indicated in trials of 20 DxP crosses in Indonesia (Purba et al, 1994) and in E. oleifera x E. guineensis hybrids in Malaysia (Chung et al, 1994). Thus, resistant materials view as an outstanding promise for future management of BSR in oil palm in SEA (Breton et al, 2006;Durand-Gasselin et al, 2005;Idris et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Field observations in North Sumatra disclosed that E. guineensis of Deli origin from Malaysia and Indonesia were more susceptible than African material (Durand-Gasselin et al, 2005), and other trials have revealed differences in susceptibility, indicating possible genetic resistance within host populations (Breton et al, 2006;Idris et al, 2004). The existence of resistant genotypes has also been indicated in trials of 20 dura x pisifera (DxP) crosses in Indonesia (Purba et al, 1994) and in E. oleifera x E. guineensis hybrids in Malaysia (Chung et al, 1994). Thus, resistant materials are viewed as an outstanding promise for future management of BSR in oil palm in SEA (Breton et al, 2006;Durand-Gasselin et al, 2005;Idris et al, 2004) and there are ongoing works in Sumatera and Socfindo in Indonesia.…”
Section: P R E S Smentioning
confidence: 99%
“…Pelatihan sejenis yang dilaksanakan dengan metode ceramah atau penyampaian materi dan praktek/pelatihan pada guru dengan materi analisis SWOT menunjukkan hasil adanya peningkatan pengetahuan peserta. (Purba, Purba, Sipayung, Girsang, & Saragih, 2022) Aspek kedua terkait materi pelatihan dinilai mayoritas baik oleh peserta pelatihan. Alasan peserta memberikan penilaian baik karena materi yang disampaikan membantu kebutuhan di kelas.…”
Section: Hasil Dan Pembahasanunclassified
“…Nilai ekonomi yang didapat dari hasil kelapa sawit antara lain sebagai penunjang perdagangan luar negeri, pemasok tenaga kerja, dan sebagai sumber penghasilan masyarakat setempat. Menurut Purba & Sipayung (2017) dan Ngadi & Noveria (2017), dampak positif yang diberikan dengan adanya perkebunan kelapa sawit yakni sebagai sumber pendapatan dan menciptakan peluang kerja serta berkontribusi terhadap pembangunan daerah.…”
Section: Abstrakunclassified